Emergy investigation of carbon dioxide utilization processes for methanol synthesis. Issue 4 (August 2022) - Nimmanterdwong, Prathana; Piumsomboon, Pornpote; Chalermsinsuwan, Benjapon
Abstract: CO2 to methanol (C2M) technology has been a promising sustainable solution with negative carbon emissions. A suitable indicator is needed to ensure that it demonstrates the progress in moving toward a zero-net emission. This study proposed an emergy analysis of three alternative methanol productions from captured CO2 . These are methanol from direct hydrogenation with hydrogen from natural gas reforming (Case 1), methanol from direct hydrogenation with hydrogen from water electrolysis (Case 2), and methanol from CO2 /NG/steam-mixed reforming (Case 3). The highest emergy consumption per joule methanol (with a transformity of 2.93 ×10 5 sej/J) was Case 2. According to emergy distribution, the emergy input that dominates each case study includes; natural gas (as raw material and fuels) in Case 1 and Case 3 and electricity for water electrolysis in Case 2. When comparing transformity with conventional methanol production from fossil fuel, the CO2 to methanol processes could compete with the traditional one. Moreover, with the implementation of renewable electrical sources (wind power), the transformity of Case 2 could be reduced to 4.95 × 10 4 sej/J and became lower than the methanol production from biomass (7.87 ×10 4 sej/J). This improvement leads Case 2 to be the preferable choice for methanol production. Graphical Abstract: ga1 Highlights: Emergy is used to find CO2 to methanol performance in term of natural investment. The transformity of three alternative processes are lower than the fossil-based. Natural gas consumption dominates methanol from steam methane reforming. CO2 -utilized gas-to-methanol process is mainly affected by natural gas consumption. Renewable source substitution makes CO2 to methanol be competitive to bio-methanol.